Investigating the Role of Digital Arts in Decolonizing Knowledge and Promoting Indigenous Standpoints (Journal of the Digital Humanities Association of Southern Africa, 2024)
Preliminary studies indicate that African educational systems reflected their socio-cultural being, and fit into the moral, economic and physical developments of its generation before colonial inception. Marker (2011) noted that education is one of the significant tools for colonial exploitation in Africa. Even in this post-colonial era, the contemporary African education or knowledge system is predominantly centered on foreign educational structures and standpoints. This undermines or alters the focus of African belief systems and culture. Africans must preserve and promote their traditional knowledge-based system regardless of its co-existence with foreign education in order to sustain and restore their self-respect and total emancipation. In order to elevate the rich cultural heritage of Africans and to promote the indigenous perspective, there must be a paradigm shift from foreign epistemologies to a decolonized knowledge-based system. Decolonizing knowledge is an effort to theorize one traditional knowledge system and entrench into the imposed foreign epistemology theories and interpretations in order to promote indigenous standpoints. According to Dreyer (2017), it seeks to construct and legitimize other knowledge systems by exploring alternate epistemologies, ontologies, and methodologies. The purpose of this paper is to explore the role of visual narratives/digital storytelling within Digital Arts in decolonizing knowledge and promoting indigenous African cultures and viewpoints. An exploratory research approach through a narrative literature review was utilized to come out with scholarly suggestions from the stance of digital arts researchers. Additionally, an oral interview was conducted to seek views from Digital Arts professionals and researchers.
Keywords: Culture; Folktale Animation; Decolonizing Knowledge; Storytelling; Visual Narratives